Hukum Ketenagakerjaan sebagai Pelindung bagi Tenaga Kerja dan Pengusaha dalam Penanganan Masalah Hubungan Kerja - Ariayuda, Satria; Maharani, Eva Naura; Akbar, Afriansyah Mufthi; Yohana Sinaga, Romauli (UNIVERSITAS SERAMBI MEKKAH, 2025)
To protect employers and workers, employment law provides fair and balanced regulations. In Indonesia, Law 13/2003 and the Job Creation Law regulate employment with the aim of guaranteeing workers' rights such as decent wages, rest periods, and protection from discrimination, as well as providing legal certainty for employers. In this article, we will explore the various ways in which the application of employment law can address employment disruptions, improve labor protection, and support socio-economic stability. Due to the transformation of the world of work caused by globalization and digitalization, regulations must be adjusted to ensure that industrial relations remain stable. With a comprehensive approach, employment law is expected to create a balance between company productivity and labor welfare, which will drive the nation's long-term growth.